Management of unusual metallosis and failed elbow replacement in rheumatoid female: a case report - Nahar, Kuldeep; Nahar, Nikita (International Journal of Research in Orthopaedics, 2020)
42 years old female who was operated for rheumatoid arthritis elbow right side with revision of total replacement. Her elbow was primarily replaced 10 years before this surgery. She had severe metallosis and breakage of ulnar stem, loosening of cement (ulnar). Humerus stem was well fixed. Massive metal debris in soft tissue was removed. humerus side cement and stem were removed by splitting the bone. Revision stem was fixed with cement and circumferential wiring. On 6 yrs following surgery, patient is doing well in terms of pain relief and range of motion around elbow. She is doing almost all activities of daily life. Early detection and removal primary implant are the need of hour to save the ill effects of metallosis and bone resorption.